Cow urine, Indian yellow, and art forgeries: An update. (July 2017) - Smith, Gregory Dale
Abstract: In a recent technical note in this Journal, de Faria et al., 2017 [1] reported the Raman spectrum of authentic Indian yellow artists' pigment, correcting a decades old reference spectrum that has led to the misidentification of this pigment in artworks that actually contained tartrazine yellow. The present communication provides additional information and corrects important experimental details mentioned by de Faria et al. that should lead to further identifications of the authentic pigment in artworks. Despite their claim that the analysis of this naturally fluorescent colorant is only possible with Fourier transform (FT) instruments, the ready characterization of two authentic samples of historic Indian yellow pigment is demonstrated here using commonly available visible and near-infrared excitation sources on a dispersive Raman microspectrometer. To highlight the importance of the proper identification of dyes and colorants, the authentication and art historical implications of previous literature reports that have misidentified Indian yellow on historic documents are more thoroughly discussed here from a forensic science point of view. The numerous modern pigments that are sold as imitation Indian yellow are addressed and analyzed, allowing the ready noninvasive detection of anachronistic colorants in attempted forgeries. Finally, this unusual pigment is positively identified for the first time using non-invasive dispersive Raman microspectroscopy on a historic object of uncertain date, a highly decorative manuscript from the Indian subcontinent.